Open‐label study of oral CEP‐701 (lestaurtinib) in patients with polycythaemia vera or essential thrombocythaemia with JAK2‐V617F mutation. (28th October 2013) - Hexner, Elizabeth; Roboz, Gail; Hoffman, Ron; Luger, Selina; Mascarenhas, John; Carroll, Martin; Clementi, Regina; Bensen‐Kennedy, Debra; Moliterno, Alison
Summary JAK2‐V617F is central to the pathogenesis of myeloproliferative neoplasms. We examined whether lestaurtinib decreased JAK2‐V617F allele burden and evaluated its clinical benefits and tolerability in patients with polycythaemia vera (PV) and essential thrombocythaemia (ET). This phase 2, open‐label, multicentre study was designed to detect ≥15% reduction in JAK2‐V617F allele burden in 15% of patients. Eligible patients received lestaurtinib 80 mg twice daily for 18 weeks and could participate in a 1‐year extension phase of treatment. Of 39 enrolled patients, 27 (69%) had PV; 12 (31%) had ET. While the pre‐specified responder rate of 15% was not met, lestaurtinib modestly reduced JAK2‐V617F allele burden and reduced spleen size in a subset of patients. Of 37 patients in the full efficacy analysis, 5 (14%) responded clinically. Every patient had ≥1 adverse event, most commonly gastrointestinal (95%). Fifteen patients (38%) experienced serious adverse events; 23 (59%) withdrew due to adverse events. This is the first reported study of JAK2‐inhibitor treatment in patients with PV/ET and highlights both the need for further studies to assess the role of JAK2 inhibition in treatment of PV/ET and the use of JAK2‐V617F as a biomarker for response. This trial was registered at www.clinicaltrials.gov as NCT00586651.